Recommendations for Systemic Antimicrobial Therapy in Fracture-Related Infection: A Consensus From an International Expert Group - Depypere, Melissa (J Orthop Trauma, 2020)
SUMMARY: Fracture-related infection (FRI) is a major complication in musculoskeletal trauma and one of the leading causes of morbidity. Standardization of general treatment strategies for FRI has been poor. One of the reasons is the heterogeneity in this patient population, including various anatomical locations, multiple fracture patterns, different degrees of soft-tissue injury, and different patient conditions. This variability makes treatment complex and hard to standardize. As these infections are biofilm-related, surgery remains the cornerstone of treatment, and this entails multiple key aspects (eg, fracture fixation, tissue sampling, debridement, and soft-tissue management). Another important aspect, which is sometimes less familiar to the orthopaedic trauma surgeon, is systemic antimicrobial therapy. The aim of this article is to summarize the available evidence and provide recommendations for systemic antimicrobial therapy with respect to FRI, based on the most recent literature combined with expert opinion. LEVEL OF EVIDENCE: Therapeutic Level V. See Instructions for Authors for a complete description of levels of evidence.